The use of salivary specimen for COVID-19 detection using RT-PCR assay: a systematic review - Kevin Chrisanta Budiyatno; Adik Wibowo; Samuel Lay Riwu (International Journal of Public Health Science (IJPHS), 2022)
As coronavirus disease 2019 (COVID-19) cases arose globally, active case finding by performing throat swab test proposed high risk for the healthcare workers. Saliva had recently been reported to show positive detection means for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and proposed advantages of self-collection, less requirement of transport media, and reduced nosocomial transmission risk. However, support evidence regarding its diagnostic value was still lacking and varied widely in specimen collection method. This systematic review aimed to assess the diagnostic value of salivary specimens (SS) for COVID-19 detection using reverse transcription polymerase chain reaction (RT-PCR) assay compared with throat swab specimens (TSS), while putting into consideration confounders such as patients’ initial condition, specimen collection method, and transport media used. Six databases were used for identifying relevant studies. Final search yielded 19 eligible studies which was reviewed based on the major outcome: diagnostic agreement, sensitivity & specificity, and viral load comparison. The use of SS as an alternative to TSS showed to be promising although specimen collection method needed to be standardized. SS was comparable to TSS in detecting COVID-19 using RT-PCR assay, especially in symptomatic or confirmed cases. More Randomized controlled trials (RCTs) were still needed to clearly demonstrate the ability of SS to capture asymptomatic cases in the setting of mass surveillance, where patients would self-collect the specimen at ease.